2015
DOI: 10.1007/s12687-015-0245-1
|View full text |Cite
|
Sign up to set email alerts
|

Rural Mexican-Americans’ perceptions of family health history, genetics, and disease risk: implications for disparities-focused research dissemination

Abstract: Disseminating the results of transdisciplinary health disparities research will increasingly involve discussing family health history and/or genetic information with study participants and their communities. Often, individuals' familiarity and comfort with these topics will be unclear. To inform the dissemination activities of a Center for Population Health and Health Disparities (CPHHD) studying multilevel determinants of breast cancer disparities in Latinas, we talked with Spanish-speaking Mexican-Americans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 28 publications
1
12
1
Order By: Relevance
“…14 Within the Centers for Population Health and Health Disparities, investigators from the Partnership to Understand and Eliminate Disparate Outcomes (PUEDO) at the Fred Hutchinson Cancer Research Center are partnering with Mexican American women to explore the women’s ancestry and breast cancer and the role of genetic testing in reducing breast cancer disparities between Mexican American and white women. 15 …”
Section: Using Genetics To Combat Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…14 Within the Centers for Population Health and Health Disparities, investigators from the Partnership to Understand and Eliminate Disparate Outcomes (PUEDO) at the Fred Hutchinson Cancer Research Center are partnering with Mexican American women to explore the women’s ancestry and breast cancer and the role of genetic testing in reducing breast cancer disparities between Mexican American and white women. 15 …”
Section: Using Genetics To Combat Diseasementioning
confidence: 99%
“…15 In a linked project, investigators will examine the ancestral heterogeneity of study participants (with European, American Indian, and African ancestry) and test for relationships between the genetic markers that reflect ancestral origins and disease. Such research will inform individualized assessment of risk and facilitate health care that is more appropriate than current care.…”
Section: Using Genetics To Combat Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…For example, we struggled with how to disseminate the different types of results that PUEDO may produce, which range from novel genetic associations to statistical assessments of intervention efficacy and cost effectiveness, in a way that is transparent, but also contextualized within the larger evidence base, so as to not contribute to hype or misinformation. 21,22 We relied on our CAB’s input and expertise to address this issue— they, along with the FHCRC Institutional Review Board, will review all dissemination materials. Returning to participants for their input, as our CAB originally suggested, would be ideal, but in some ways scientifically compromised if dissemination materials are based on well-validated approaches and tested theories.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly true for immigrant populations who may be from countries where education is not a right, but a privilege for those who can afford it. For example, Malen, Knerr, Delgado, Fullerton, and Thompson () found that none of the participants in their study of rural Mexican‐Americans could describe what “genetics” meant to them in their own words. In a study of low‐income Chinese immigrants, there was skepticism regarding genetic causes of cancer, with much stronger beliefs about environmental causes (Cheng et al, ).…”
Section: Challenges and Opportunities For Genetic Counselorsmentioning
confidence: 99%